PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK KELAS XI MIPA SMA NEGERI 4 PADANG - Annisa Urahmi (Departemen Matematika, 2020)
Learning outcomes are obtained by students after learning activities. Proper learning is needed in improving learning outcomes. But in its application, the process of learning mathematics at SMAN 4 Padang is still centered on the teacher which causes learning activities that are less than optimal. Activities and learning outcomes in mathematics can be improved by applying the discovery learning model. The purpose of this study is to find out and explain whether the activities and learning outcomes of experimental class students are better than the control class. This type of research is a combination of quasi-experimental and descriptive experiments with static group design research. Based on the results of the study it can be concluded that the activities of students who learn with discovery learning models tend to increase and the results of learning mathematics students who learn with the discovery learning model are better than students who learn with conventional learningKeywords — Discovery learning, Learning activities, Learning outcomes